APLIKASI TEKNIK HAPA ZOME PADA PAKAIAN SEBAGAI BAGIAN KAMPANYE GO GREEN - -, sarwono -; Affanti, Tiwi Bina; santoso, ratna endah; Josef, adji Isworo (Institut Seni Indoensia Surakarta, 2020)
The purpose this training activities is to provide skills for neglected and drop-out children at PPSA Taruna Yodha Sukoharjo in making clothing decorations with hapa zome techniques and marketplace marketing. Currently, there is an eco fashion trend in society. Clothes with hapa zome decorative techniques are considered unique but not many have made them. Hapa zome material can easily be obtained from plants in the environment which is usually as weeds. The activities carried out by the method of lectures, tutorials, practice and product evaluation. The activity ran smoothly, the atmosphere was fun and the participant’s interest in participating in the training was very high. The participants seemed able to develop various models of natural decoration on clothes and mix them with embroidery techniques. This training has the impact of increasing the participant's ability to make clothing decorations with the hapa zome technique and to understand several marketplace marketing techniques. The product was produced as part of the go green campaign and it predicted have a good market. Key words: go green. hapa zome, Taruna Yodha,